ANALISIS PROFITABILITAS PERBANKAN SYARIAH DI NEGARA OKI - Hanifah, Zalfa Elvina Dewi; Zuhroh, Idah (Journal of Financial Economics & Investment, 2024)
The development of the economic system can be seen from the movement of the financial system which has a global impact. Therefore, the role of banking is very important for economies around the world. The aim of this research is to assess the financial performance of Islamic banks in OIC member countries (Indonesia, Malaysia, Pakistan, United Arab Emirates and Saudi Arabia) through profitability. The measure of profitability is to use the ROA ratio. The data was processed using panel data regression testing. The results of data analysis show that CAR and sukuk have a significant positive effect on profitability, while BOPO has a significant negative effect on the profitability of sharia banks in OIC member countries during the 2018 - 2022 period. Only the inflation variable has not significantly influenced the profitability of sharia banks in OIC member countries during the period. 2018 – 2022. The implication of this research is that Islamic banks must strive to increase the CAR ratio and reduce the BOPO ratio because it can significantly affect the level of bank profitability. Apart from that, Islamic banks also continue to increase sukuk issuance because it can encourage increased profits.